2019
DOI: 10.4103/ams.ams_138_18
|View full text |Cite
|
Sign up to set email alerts
|

Orthopantomography and cone-beam computed tomography for the relation of inferior alveolar nerve to the impacted mandibular third molars

Abstract: Context: Relation of inferior alveolar nerve to the impacted mandibular third molars (IMTMs). Aims: The aim of this study was to assess the reliability of seven specific radiographic signs of mandibular third molar root that are observed on orthopantomography (OPG) and to predict the proximity and the absence of corticalization between the mandibular canal and IMTM root on cone-beam computed tomography (CBCT) images. Settings and Design: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
8
1
2
Order By: Relevance
“…Similar to our case, canal deviation and interruption of white lines were associated with loss of canal cortication on CBCT in a very recent study, indicating the sensory consequences of a direct contact between the roots and the mandibular canal which required further assessment prior to extraction ( 27 ). Contrary to another recent study ( 28 ), our case report showed good reliability of radiographic signs seen on OPG on predicting the proximity of the third mandibular root with the mandibular canal, when related to CBCT findings. These complications are considered profoundly serious both because of the medical and psychological sequalae, not to mention the possible legal consequences.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our case, canal deviation and interruption of white lines were associated with loss of canal cortication on CBCT in a very recent study, indicating the sensory consequences of a direct contact between the roots and the mandibular canal which required further assessment prior to extraction ( 27 ). Contrary to another recent study ( 28 ), our case report showed good reliability of radiographic signs seen on OPG on predicting the proximity of the third mandibular root with the mandibular canal, when related to CBCT findings. These complications are considered profoundly serious both because of the medical and psychological sequalae, not to mention the possible legal consequences.…”
Section: Discussioncontrasting
confidence: 99%
“…Of all the images with two or more signs on OPG, darkening of roots in combination with interruption in the white line (2.3%) was noted in most of the cases. Similar findings were noted by Ghai and Choudhury, [ 8 ] Neves et al [ 10 ], and Saha et al [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…The most recent, consecutive 50 articles containing “inferior alveolar canal” or “inferior alveolar nerve canal” were included (defined as the IAC/IANC group) (Adibi, Shahidi, Nikanjam, Paknahad, & Ranjbar, 2017; Afsa & Rahmati, 2017; Al‐Ekrish et al, 2018; Al‐Ekrish et al, 2020; Ali, Mosleh, & Shawky, 2018; Aljarbou, Aldosimani, Althumairy, Alhezam, & Aldawsari, 2019; Arbel et al, 2019; Atef & Mounir, 2018; Česaitienė, Česaitis, Junevičius, & Venskutonis, 2017; Y. Chen, Liu, Pei, Liu, & Pan, 2018; Clark, Barbu, Lorean, Mijiritsky, & Levin, 2017; Demirel & Akbulut, 2020; Dutra et al, 2019; Elkhateeb & Awad, 2018; Ghai & Choudhury, 2018; Goller Bulut & Köse, 2018; Gumusok, Alkurt, Museyibov, & Ucok, 2016; He, Wang, Hu, & Liu, 2019; Ishii, Abe, Moro, Yokomizo, & Kobayashi, 2017; Kablan, Abu‐Sobeh, Lorean, & Levin, 2020; Khojastepour, Khaghaninejad, Hasanshahi, Forghani, & Ahrari, 2019; Kubota, Imai, Nakazawa, & Uzawa, 2020; S. Lee, Lee, Kim, & Nam, 2019; Liu, Sidell, Huon, & Torre, 2018; Luangchana, Pornprasertsuk‐Damrongsri, Kitisubkanchana, & Wongchuensoontorn, 2019; Mortazavi, Baharvand, & Rezaeifar, 2018; Mortazavi, Baharvand, Safi, & Behnaz, 2019; Mortazavi, Baharvand, Safi, Dalaie, et al, 2019; Patil, Pai, Vineetha, Rajagopal, & Dkhar, 2019; Patrick, Birur, Gurushanth, Raghavan, & Gurudath, 2017; Pour, Sedaghati, & Shamshiri, 2020; Prakash et al, 2018; Qi et al, 2019; Rytkönen & Ventä, 2018; Saha, Kedarnath, & Singh, 2019; Şahin, Odabaşı, Demiralp, Kurşun‐Çakmak, & Aliyev, 2019; Sharifi, Beshkar, Mobayeni, & Hasheminasab, 2018; Shokry et al, 2019; Sirin, Yildirimturk, Horasan, & Guven, 2020; Tabrizi et al, 2019; Tachinami, Tomihara, Fujiwara, Nakamori, & Noguchi, 2017; Tudtiam et al, 2019; Uchida, Motoyoshi, Namura, & Shimizu, 2017; Uzun, Sumer, & Sumer,…”
Section: Methodsmentioning
confidence: 99%